Organizacja produkcji i wyniki ekonomiczne gospodarstw ekologicznych o różnej wielkości - Komorowska, Dorota (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The paper presents the impact of production organization on economic performance of organic farms of different size groups. With an increase in farms’ size, their profitability measured by the level of income per unit area of agricultural land deteriorates. This results mainly from the organization of crop production, namely undertaking labor-intensive crops of vegetables, fruits and potatoes, primarily in smaller farms.